Gender Gaps in Unemployment Rates in OECD Countries - Azmat, Ghazala; Güell, Maia; Manning, Alan (Journal of Labor Economics, 2006)
In some OECD countries the male and female unemployment rates are very similar but in others (notably the Mediterranean countries) the female unemployment rate is much higher than the male. Explaining these cross‐country differences is the subject of this article. We show that, in countries where there is a large gender gap in unemployment rates, there is a gender gap in both flows from employment into unemployment and from unemployment into employment. We conclude that differences in human capital accumulation between men and women interacted with labor market institutions is an important part of the explanation.